Evil, law and the state : perspectives on state power and violence - Parry, John T., 1964- (At the interface/probing the boundaries ;, 2006)
The topic of "evil" means different things depending upon context. For some, it is an archaic term, while others view it as a central problem of ethics, psychology, or politics. Coupled with state power, the problem of evil takes on a special salience for most observers. When governments do evil -in whatever way we define the term - the scale of harm increases, sometimes exponentially. The evils of state violence, then, demand our attention and concern. Yet the linkage of evil with state power does not resolve the underlying question of how to understand the concepts that we invoke when we use